SOME ASPECTS OF BELIEFS AND BEHAVIOURS THAT CONTRIBUTE TO A HEALTHY LIFESTYLE OF ADOLESCENTS STUDYING AT SCHOOL - Habriella V. Dudash; Valeriya V. Brych; Mariana М. Dub (Клінічна та профілактична медицина, 2025)
Introduction. Engagement of adolescents in health-promoting behaviour requires creating favourable conditions to shape their personal desire to maintain a healthy lifestyle and recognise their own health as the greatest value. Organising an intervention system which changes adolescents’ beliefs in order to modify their lifestyle requires information about the current situation regarding their knowledge about health, beliefs in the necessity of health-preserving skills, and the behaviour they practice every day.